EFFECT OF INCLUSION CALCIUM-PALM FATTY ACID (Ca-PFA) ON GROWTH PERFORMANCE AND PROFILE OF BODY FATTY ACID OF BROILER - Dewi, G.A.M.K; Astawa, P.A.; Sumadi, I.K. (Diponegoro University, 2011)
A study of effect of inclusion of calcium-palm fatty acid (Ca-PFA) in the diets on growthperformance and profile of body fatty acid has been conducted for 4 weeks in broiler. A total of 160birds were used in present experiment which was arranged in a Completely Randomized Design with 4treatments and 5 replications (8 birds each). Dietary inclusions of Ca-PFA of 0, 5, 10 and 15% werereflected as R0, R1, R2 and R3, respectively. Results of the experiment showed that growth performancebased on the feed consumption significantly decreased (p<0.05), but there were no significant (p>0.05)effect for final body weight, carcass percentage and carcass composition. The inclusion of Ca-PFA in thediet was not affected the saturated fatty acid (p>0.05), but showed significant effect on unsaturated fattyacid and omega-3 fatty acid (p<0.05). Body fat distribution was not affected by inclusion level of Ca-PFA at a level of 15%. In conclusion, the inclusion of Ca-PFA in the diet until 15% decreased feedconsumption and produced similar growth performance, however it increased unsaturated fatty acid,omega-3 fatty acids and decreased body fat of broiler.